Comparison of the hydrocolloids Nostoc commune and Nostoc sphaericum: Drying, spectroscopy, rheology and application in nectar - Torres-Maza, Antony (2020)
Present work proposes the substitution of traditional food stabilizers from the hydrocolloids of algae. Hydrocolloids from Nostoc commune and Nostoc sphaericum were extracted, characterized by infrared spectroscopy, and modelled their rheological behavior. The dried extract samples were dried by lyophilization and hot air and diluted in water at concentrations of 0.15% and 0.25% and lastly stored at different temperatures (7 – 80 °C). The infrared indicated C – O – C vibrations corresponding to the glucose cycle (1020 cm-1) and C = O of carboxyl groups (1950 cm-1) are proper of hydrocolloids. Rheological models of Bingham, Ostwald and Herschel-Bulkley confirmed that the Nostoc coomune species presents a higher coefficient of plastic viscosity (η) and coefficient of consistency (k) than Nostoc commune; the freeze drying method had a positive influence and significant on these results (p < 0.05). Likewise, the hydrocolloid samples were diluted under nectar conditions (12 °Brix and 4.5 pH) taking carboxymethyl cellulose (CMC) as a control, finding that there is less influence of temperature on the consistency index of hydrocolloids in the order of Nostoc sphericum < Nostoc commune < CMC. It is concluded that the application of hydrocolloids of the genus nosctoc can be used as additives in the preparation of nectar, maintaining their rheological properties.